If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 48 = 3 + 9x Solving 48 = 3 + 9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9x' to each side of the equation. 48 + -9x = 3 + 9x + -9x Combine like terms: 9x + -9x = 0 48 + -9x = 3 + 0 48 + -9x = 3 Add '-48' to each side of the equation. 48 + -48 + -9x = 3 + -48 Combine like terms: 48 + -48 = 0 0 + -9x = 3 + -48 -9x = 3 + -48 Combine like terms: 3 + -48 = -45 -9x = -45 Divide each side by '-9'. x = 5 Simplifying x = 5
| 2x+x+5=70*2 | | 16/36=z/54 | | 1/3x-1/5=-1/2 | | 2x+x+5=70 | | (2y-2)+2(y-3)=25 | | [x-1]+2= | | (x-2)+2(y-3)=22y | | -8+2=18 | | 2x^2=(x+2)(x-3)+12 | | (x-2)+2(y-3)=25 | | 1/x-1/y=7/2 | | 6x+27=13x-37 | | 18w=19 | | 15y=14(y+17) | | r+13=19 | | 20d=17 | | n+-1=6 | | 3(2x+8)=-4x+4 | | 8x+17-7x=-5+(-10) | | x+70=25 | | 4*4x=32.5 | | 7+(-13)=3x-6-2x | | 4x+x+2=-26-2x | | (2y-2)+(y-3)=21 | | -8x+9+9x=-6+1 | | (2y-2)+(y-3)=25 | | 16x=32.5 | | 4(x+2)=-26-2x | | Y+4.9=-6.1-4.6 | | (x-2)+(y-3)=25 | | 5+6-0+10= | | -1+9=m-1 |